Pengaruh Social Media Marketing dan Labelisasi Halal Terhadap Keputusan Pembelian Produk Wardah - Yuni Ayu Safitri; Zulfan Yusuf; Sarboini Sarboini; Edi Saputra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of social media marketing and halal labeling on purchasing decisions for Wardah products. In the current digital era, social media represents a crucial strategy for product promotion, particularly among young consumers. Furthermore, halal labeling plays a significant role in attracting Muslim consumers who are increasingly conscious of the importance of Sharia-compliant products. The study employs a quantitative survey method, gathering data through questionnaires distributed to Wardah consumers. Multiple linear regression analysis was used to measure the impact of each variable on purchasing decisions. The results indicate that social media promotion has a positive and significant effect on purchasing decisions, with consumers more inclined to purchase products advertised on social media. Additionally, halal labeling was found to have a positive influence, as consumers prefer products with halal certification. This study encourages marketers to leverage social media and ensure product compliance with halal standards as a strategy to boost sales.